The Use of Technology Bloom's Taxonomy in Formative and Summative Evaluation: A Systematic Literature Review - Dwi Pangga; I Gede Ratnaya; I Gusti Lanang Agung Parwata; I Dewa Ayu Made Budhyani; Salma Hasna Hamiydah (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study aims to systematically examine the use of Bloom's Taxonomy in formative and summative evaluations as an important instrument for measuring student learning outcomes. The revised Bloom's Taxonomy offers a systematic cognitive framework from levels C1 (remembering) to C6 (creating), which can be used as a basis for developing valid and meaningful evaluations. Method: This study was conducted using a systematic literature review method on 30 articles published between 2020 and 2025. The analysis results indicate that the application of Bloom's Taxonomy in formative evaluations is still dominated by lower cognitive levels (C1-C2), despite efforts to strengthen the approach to higher-order thinking. Meanwhile, Bloom-based summative evaluations have demonstrated increased validity and alignment with learning outcomes, particularly through the use of rubrics and authentic assessments.  Results:  This study also identified various challenges, such as low teacher competency in developing taxonomy-based instruments and the suboptimal integration of technology, including artificial intelligence, to support adaptive evaluation. Nevertheless, several practical strategies were identified, such as teacher training, the use of competency-based question banks, and the development of digital-based project evaluations.  Novelty: The integration of Bloom's Taxonomy into learning evaluation has significant potential to improve assessment quality, mainly if supported by systemic policies, ongoing training, and technological innovation. This research provides a conceptual contribution to the development of an evaluation system that is fair, objective, and relevant to the needs of 21st-century education.